Rheumatic Diseases: Pathophysiology, Targeted Therapy, Focus on Vascular and Pulmonary Manifestations - Ruaro, Barbara; Salton, Francesco; Confalonieri, Paola (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This e-book summarises the latest advances in the rheumatic diseases with a focus on the recent efforts of vascular and pulmonary manifestations and anticipate the new and future directions of these research topic. Rheumatic diseases represent a heterogeneous group of severe autoimmune disorders. The present Special Issue aims to provide an overview of the complexity of vascular and pulmonary manifestations of rheumatologic diseases and helps in knowledge to manage them. The eleven published articles here collected underline the complexity of rheumatic diseases and the difficult to treated them. The manuscripts provide an overview of the pathophysiology and current treatment regimes of these disorders, highlighting tools which assist with diagnosis, risk stratification and therapy. Finally, we underline the importance of a multidisciplinary team working using the skills of clinicians, radiologists, and pathologists.